If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3 + -1x) + 15 = 2 (3 * -1 + -1x * -1) + 15 = 2 (-3 + 1x) + 15 = 2 Reorder the terms: -3 + 15 + 1x = 2 Combine like terms: -3 + 15 = 12 12 + 1x = 2 Solving 12 + 1x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 1x = 2 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 2 + -12 1x = 2 + -12 Combine like terms: 2 + -12 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| x+2x=x+175 | | f+2=9 | | 4h+24=6k-10 | | 12h+6=3(2+4h) | | .66x+18=90 | | -92=-6x+5(3x-4) | | 6u+6=8u+8 | | -(x-8)+3x=2(x+4) | | -22+15-22z=31 | | 33-2(16.5)= | | 15-w/4=-28 | | 160=9x+8x+10 | | r-10=14 | | 18-2(16.5)= | | 6(3d+2)-8=40 | | 4s+9=7x | | 2(-x+6)+4x-x=2x+8 | | 5z=65464 | | 18-2(16-5)= | | 3x-26=15+3x | | 2(y+1)+13=57 | | -6+4=-38 | | 2x-(4-3x)-9=x-(-4x-3)+8 | | -4(2-x)+5=12 | | .5x+1=5 | | 1+5x-40=7-1x | | 9x-7=7(2x-11) | | sin(2x)-cos(x)-(2sin(x))+1=0 | | 3x-2=45 | | 2(x+3)+7=10 | | 5z+8=7 | | 5x-17=-82 |